"Daddy's Head Is Broken": The Treatment of Children of Severe Alcoholics. Issue 1 (1st January 2021) - Brady, Mary T.
ABSTRACT: The author explicates the complex family relationships of children of severe alcoholics, and internalizations of these relationships, which can be addressed in the treatment of children and in corollary parent work. Children of serious alcoholics (or other substance use disorders) share features with other children whose parents are troubled. However, the author suggests that it is useful to consider what children of severe alcoholics have in common. Children of serious alcoholics can experience the substance of abuse as a mysterious potion, which their alcoholic parent prefers to them. Additionally, alcoholics (along with other substance abusers) expose their children to the specific results of inebriation or withdrawal from alcohol. The author discusses the following common experiences of the children of severe alcoholics: extreme difficulty in understanding parental addiction, particularly for very young children; an unconscious struggle to repair the damaged parent and to try to protect that parent from strain; and guilt at the often-necessary exclusion of the addicted parent from the household unit. Another confusing issue is mourning for a parent who is still alive and in some contact, yet severely impaired. The author describes parent work in these situations (collateral to a child psychoanalysis or psychotherapy), both with the "co dependent" parent and the alcoholic parent.